2018
DOI: 10.1186/s12870-018-1535-7
|View full text |Cite
|
Sign up to set email alerts
|

Expansin genes expression in growing ovaries and grains of sunflower are tissue-specific and associate with final grain weight

Abstract: BackgroundGrain weight (GW) is a key component of sunflower yield and quality, but may be limited by maternal tissues. Cell growth is influenced by expansin proteins that loosen the plant cell wall. This study aimed to identify spatio-temporal expression of EXPN genes in sunflower reproductive organ tissues (ovary, pericarp, and embryo) and evaluate correlations between reproductive organ growth and expansin genes expression. Evaluations involved eight different developmental stages, two genotypes, two source-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 84 publications
(97 reference statements)
0
9
0
Order By: Relevance
“… Lizana et al (2010) observed that TaExpA6 accumulates in the early grain development period, implying their role in determination of grain size in wheat. Castillo et al (2018) have shown that expansins are involved in the extension of grain tissue, and their expression is associated with the grain size of sunflower.…”
Section: Discussionmentioning
confidence: 99%
“… Lizana et al (2010) observed that TaExpA6 accumulates in the early grain development period, implying their role in determination of grain size in wheat. Castillo et al (2018) have shown that expansins are involved in the extension of grain tissue, and their expression is associated with the grain size of sunflower.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the identification of more expansins at the cellularization step, and the presence in both the endosperm and outer layers. Moreover, the role of expansins in grain is reinforced by a recent study suggesting that expansin genes could be specifically involved in grain enlargement and may control seed growth in sunflower at the early phases of development [63]. As in wheat, several DUF538 were identified in the developing grain of B. distachyon [25].…”
Section: Discussionmentioning
confidence: 92%
“…More studies on the expansin gene function had been carried out in several laboratories via gene expression (Castillo et al, 2018) and gene transformation experiment (Zenoni et al, 2011). The results really confirmed the important role of expansin genes in plant growth and development and environmental adaptation process from different perspectives.…”
Section: Discussionmentioning
confidence: 69%